The practice of Chinese medicine in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University - Baxter, Kim Gloria (Massey University, 1997)
Chinese medicine has been practised throughout history in a variety of forms in a variety of countries. This study is concerned with discovering the particular form Chinese medicine has assumed in New Zealand. Data was collected by means of an ethnographic survey of 39 practitioners and 130 patients of Chinese medicine from throughout New Zealand. The thesis explores three main areas: first, what types of Chinese medical practices exist in New Zealand; second, who seeks and supports Chinese medicine as a health therapy in New Zealand; third, the perspectives that practitioners and patients of Chinese medicine have on the practice of Chinese medicine in New Zealand. An attempt is made to balance quantitative results with the qualitative descriptions and observations of the research participants. Primarily this thesis has been written with the needs of the research participants in mind - to be an independent source of information for them. Currently, Chinese medicine has no legislative protection in New Zealand, and there are a great variety of practitioner groups and practitioners practising "Chinese medicine" (particularly acupuncture) here. The research findings suggest that the practice of Chinese medicine in New Zealand has many forms, and is frequently fragmented and mixed with other health therapies. It is concluded that adaptation to context, including the presence of "non-Chinese" therapies, is a positive feature of Chinese medicine that long predate its arrival in New Zealand. KEYWORDS: CHINESE MEDICINE; ACUPUNCTURE; ALTERNATIVE AND COMPLEMENTARY MEDICINES; ETHNOGRAPHY.
Keywords: Chinese medicine; Medical anthropology; New Zealand; Ethnography; Acupuncture; Alternative and complementary medicines